2020
DOI: 10.1039/c9ra09487c
|View full text |Cite
|
Sign up to set email alerts
|

Biochar derived from corn stalk and polyethylene co-pyrolysis: characterization and Pb(ii) removal potential

Abstract: Biochar is widely used as adsorbents for gaseous or liquid pollutants due to its special pore structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…The activation also brought some hydroxyl groups leading to the formation of Pb 3 (CO3) 2 (OH) 2 and additionally, the carbonate from the char bonded with lead to form PbCO 3 . These results were in accordance with the experiments results obtained at the end of the study as well [ 67 ].…”
Section: Adsorption Studies Using Co-pyrolyzed Charssupporting
confidence: 93%
See 2 more Smart Citations
“…The activation also brought some hydroxyl groups leading to the formation of Pb 3 (CO3) 2 (OH) 2 and additionally, the carbonate from the char bonded with lead to form PbCO 3 . These results were in accordance with the experiments results obtained at the end of the study as well [ 67 ].…”
Section: Adsorption Studies Using Co-pyrolyzed Charssupporting
confidence: 93%
“…One such study revealed a methylene blue removal capacity of 490 mg/g using co-pyrolyzed cyanobacteria and polyethylene wastes (20 mg adsorbent; 298 K; 500 mg/L of methylene blue solution) [ 70 ]. Another study achieved 99.5 mg lead/g removal using co-pyrolyzed corn stalk and polyethylene (0.1 g adsorbent; 298.15 K; 50 mg/L; pH 4.5) [ 67 ].…”
Section: Adsorption Studies Using Co-pyrolyzed Charsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method is most commonly used owing to its fluidity with biomass feedstock sources and flexible operating conditions. Various biomass raw materials like crab shell, 55 rice straw, eucalyptus leaves and vetiver grass, 56 Caragana korshinskii , 57 corn stalk and polyethylene, 58 etc. , have favourably been converted into porous carbons by pyrolysis.…”
Section: Synthesis Methods For Preparation Of Nanoporous Carbonsmentioning
confidence: 99%
“…Previously, corn stalk was reported proximate analysis; moisture 3.41%, ash 5.87%, volatile matter 80.77% and FC 11.95%, ultimate analysis; C 43.34%, H 6.12%, O 48.42%, N 2.12%. For lignocellulose of corn stalk consists of cellulose 38.40%, hemicellulose 35.73% and lignin 5.78% (Fan et al, 2020).…”
Section: Characterization Of Raw Materialsmentioning
confidence: 99%